Schreiben, Bildung und Gespräch : Mediale Absichten bei Baudri de Bourgueil, Gervasius von Tilbury und Ulrich von Liechtenstein - Lutz, Eckart Conrad (De Gruyter, 2013)
In the primarily oral culture of the medieval court, authors of sophisticated literary texts still took into account forms of reception beyond the words themselves, including, for example, the role of performers, who they sometimes mentioned in paratexts. They also attempted at times to inscribe reception modes in the texts themselves. These modes enlisted discussions and explanations to activate the texts. The book's discussion includes epistolary poems for a sophisticated literary circle, texts intended to educate royal recipients, and the lyrical tradition of the 'Frauendienst.'
Keywords: German literature -- Old High German, 750-1050 -- History and criticism.; German literature -- Middle High German, 1050-1500 -- History and criticism.; Littérature allemande -- 750-1050 (Vieux haut allemand) -- Histoire et critique.; Littérature allemande -- 1050-1500 (Moyen haut allemand) -- Histoire et critique.; LITERARY CRITICISM -- European -- German.; German literature -- Middle High German; German literature -- Old High German; 750-1500; Criticism, interpretation, etc.